2015
DOI: 10.1186/s12879-015-0815-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of recombinant canine adenovirus type-2 expressing TgROP18 (CAV-2-ROP18) against acute and chronic Toxoplasma gondii infection in mice

Abstract: BackgroundThe use of recombinant viral vectors expressing T. gondii antigens is a safe and efficient approach to induce immune responses against the parasite, as well as a valuable tool for vaccine development. We have previously prolonged the survival time of mice challenged with the RH strain of T. gondii by immunizing the mice with a eukaryotic vector expressing the protein ROP18 of T. gondii. We are now looking for ways to improve this vaccination strategy and enhance protection.MethodsIn this study, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…The ppoly2-CAV2-ΔE3 vector is mainly composed of the partial E3 region of CAV-2, human cytomegalovirus (hCMV) immediate-early gene promoter, polyA and the SV40 early mRNA polyadenylation signal. This vector was used for the recombined vaccine [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ppoly2-CAV2-ΔE3 vector is mainly composed of the partial E3 region of CAV-2, human cytomegalovirus (hCMV) immediate-early gene promoter, polyA and the SV40 early mRNA polyadenylation signal. This vector was used for the recombined vaccine [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we generated the recombinant canine adenovirus type 2 virus (rCAV2-HA) expressing H3N2 CIV HA protein as previously described [ 49 ]. Briefly, the HA gene (A/canine/Guangdong/01/2006 (H3N2)) was inserted into the ppoly2-CAV2-ΔE3 vector (ppoly2-CAV2-ΔE3-HA).…”
Section: Methodsmentioning
confidence: 99%
“…Two mice groups were injected intraperitoneally with 0.2 mL of physiological saline containing 1 × 10 2 T. gondii tachyzoite RH strain (type I) and labelled as infected groups. In our previous work, we have previously studied the optimal number of RH strain infections per mouse, in order to minimize damage by T. gondii infection [17]. Meanwhile, the control group was injected with an equal dose of physiological saline.…”
Section: Animals and Experiments Set-upmentioning
confidence: 99%
“…Adenovirus, which can penetrate host cells delivering vaccine antigen to antigen-presenting cells (APCs) and elicit vigorous and sustained T-cell responses, is a promising T. gondii vaccine vector and can be used effectively to transport immunogens [27]. Recent studies have also found that recombinant canine adenovirus type-2 expressing TgROP16 and TgROP18 provides partial protection against acute T. gondii infection in mice, and indicate that adenovirus vectors may be potentially useful in the development of an effective vaccine against T. gondii infection [21,22]. The mucosal immune system consisting of specialized epithelial cells can trigger both humoral and cell immune responses when antigens are administered with appropriate adjuvants or attenuated live vaccines via mucosal routes (oral, nasal, sublingual, ocular, genital, or rectal) [18,23].…”
Section: Introductionmentioning
confidence: 99%